Influence of the Addition of Polystyrene-blockpoly(methyl methacrylate) Copolymer (PS-b-PMMA) on the Morphologies Generated by Reaction-Induced Phase Separation in PS/PMMA/Epoxy Blends - Girardt Reydet, Emmanuel (2002)
Homogeneous solutions of polystyrene (PS) and poly(methyl methacrylate) (PMMA) in diglycidylether of bisphenol A, containing about 8 wt.‐% total thermoplastic, and with or without 0.5 wt.‐% of a PS‐b‐PMMA block copolymer, were polymerized in two ways (i) in the presence of a tertiary amine (benzyldimethylamine, BDMA), or (ii) using a stoichiometric amount of a diamine (4,4′‐diaminodiphenyl sulfone, DDS). A double phase‐separation was recorded by light transmission during polymerization. A PS‐rich phase was separated at low conversions and a PMMA‐rich phase was segregated at more advanced conversions. The addition of the block copolymer produced significant changes in the morphologies generated. For the BDMA‐initiated polymerization, the presence of the block copolymer made the small PMMA‐rich domains clearly discernible in transmission electron microscopy (TEM) micrographs. For the DDS‐cured system, the addition of the block copolymer led to a dispersion of small PS‐rich particles encapsulated by PMMA shells. The possibility of generating a stable dispersion of biphasic particles by polymerization‐induced phase separation opens a new way to modify thermosetting polymers for toughening purposes.